Evaluation of HSE Culture and Identification of Its Promotion Strategies in Northern Khorasan Province Gas Company - Dariush SHAHPARAST (بهداشت کار و ارتقای سلامت, 2022)
Background and Objective: Nowadays, in order to improve the level of Health, Safety and Environment (HSE) culture of employees, organizations have reached this important conclusion that the weaknesses and strengths of the system should be identified .This is done by periodically evaluating the level of HSE culture, in order to determine and apply the targeted promotion. Therefore, the aim of this research is to evaluate the level of HSE culture among the employees of Gas Company of Northern Khorasan Province. Materials and Methods: This is a descriptive-analytical, cross-sectional study conducted in 2009-2010. The questionnaires were self-administered and semi-supervised by the participants. The statistical population included 400 official, contractual and non-official employees. Simple random sampling method and Cochran formula were used to select the statistical population, which included 198 employees in all organizational levels of the company. Data were analyzed using SPSS software version 23, and descriptive statistics, inferential statistics and correlation tests. HSE culture promotion strategies were identified and presented after reviewing and analyzing the scores. Results: Compared with the determined limit using the relevant formula (number 177), in this study, the general level of HSE culture of North Khorasan Gas Company was evaluated as positive with a score of 198.42. The minimum and maximum HSE culture scores of the participants were 131 and 281, respectively. Education indicator had the most positive effect, and disregard and violation indicator in rules of HSE had the most negative effect on HSE culture score. Conclusion: The positive level of HSE culture in a high percentage of employees, compared to the defined boundary, shows successful implementation of HSE management system indicators, such as training, employees' participation, rules and instructions, and commitment of managers are priority in the company under study.